Comparison of bovine viral diarrhea virus-specific antibody responses of young beef calves vaccinated with either modified live virus or inactivated virus regimens - Erickson, Nathan (Can Vet J, 2020)
Bovine viral diarrhea virus (BVDV) is an important pathogen causally associated with morbidity and mortality, and production losses in both suckling and weaned beef calves. Vaccination for protection against disease caused by BVDV is challenging because of the inhibitory effect of maternal antibodies; however, it is most convenient for beef producers to vaccinate calves before moving herds to summer pastures. We compared modified live and inactivated vaccines used for priming and boosting beef calves and found that neither type of vaccine results in strong antibody responses in the face of maternal antibodies. These data are generally consistent with previous studies and suggest that alternative protocols using early mucosal delivery followed by parenteral boosting should be examined to improve vaccine efficacy.